2018
DOI: 10.1183/23120541.00021-2017
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of different analysis algorithms to calculate multiple-breath washout outcomes

Abstract: Lung clearance index (LCI) is the main outcome of the multiple-breath washout (MBW) test. Current recommendations for LCI acquisition are based on low-grade evidence. The aim of this study was to challenge those recommendations using alternative methods for LCI analysis.Nitrogen MBW measurements from school-aged children, 20 healthy controls, 20 with cystic fibrosis (CF) and 17 with primary ciliary dyskinesia (PCD), were analysed using 1) current algorithms (standard), 2) three alternative algorithms to detect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…The lack of transparency into the signal processing and algorithms used, lack of standardized protocol, and ease in which results can be manipulated by changing settings have made it difficult to standardize and interpret MBW outcomes from WBreath software. 7,23,24 We found that WBreath 3.28.0 underestimates the volume of re-inspired tracer gas and does not calculate FRC and LCI in accordance with MBW consensus guidelines. The revised WBreath version 3.52.3 corrects these discrepancies and facilitates reanalysis of raw infant MBW data in accordance with current consensus guidelines.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…The lack of transparency into the signal processing and algorithms used, lack of standardized protocol, and ease in which results can be manipulated by changing settings have made it difficult to standardize and interpret MBW outcomes from WBreath software. 7,23,24 We found that WBreath 3.28.0 underestimates the volume of re-inspired tracer gas and does not calculate FRC and LCI in accordance with MBW consensus guidelines. The revised WBreath version 3.52.3 corrects these discrepancies and facilitates reanalysis of raw infant MBW data in accordance with current consensus guidelines.…”
Section: Discussionmentioning
confidence: 79%
“…However, indirect measurement of SF 6 concentration, delayed tracer gas clearance from the side chambers, and fact that the main‐stream molar mass signal is highly susceptible to fluctuations in humidity and temperature means that many corrections have to be applied to the raw signal to produce a standard washout curve. The lack of transparency into the signal processing and algorithms used, lack of standardized protocol, and ease in which results can be manipulated by changing settings have made it difficult to standardize and interpret MBW outcomes from WBreath software 7,23,24 . We found that WBreath 3.28.0 underestimates the volume of re‐inspired tracer gas and does not calculate FRC and LCI in accordance with MBW consensus guidelines.…”
Section: Discussionmentioning
confidence: 88%
“…9,10 Similarly, differences between data processing algorithms and software versions have also been reported. [11][12][13][14][15] In this issue of Pediatric Pulmonology, Oestreich et al present a very comprehensive analysis of the SF 6 -MBW algorithm used in the WBreath 3.28.0 (ndd AG) software, which was historically combined with the Exhalyzer D device (Eco Medics AG). In this setup, molar mass and flow are measured and the concentration of SF 6 is indirectly estimated.…”
Section: E D I T O R I a Lmentioning
confidence: 99%
“…9,10 Similarly, differences between data processing algorithms and software versions have also been reported. [11][12][13][14][15] In this issue of Pediatric Pulmonology, Oestreich et al Firstly, different setups are not interchangeable. Secondly, in all commercial devices, technical issues of different origin bias the outcome (functional residual capacity, LCI and other measures of gas mixing efficacy).…”
Section: Multiple Breath Washout Test In Infants-still In Search For ...mentioning
confidence: 99%
See 1 more Smart Citation